Fixed Point Results for Single-valued Mappings on a Set with Two Metrics using a Dass Gupta-type Bilateral Contraction - Saeed, Amber; Ahmed, Jawad; Shabbir, Muqddas; Umair, Muhammad; Sabbir, Hossain MD; Paul, Shimul; Arfan, Mohammad; Houqe, Sheikh Muktadirul; Anowar, Hossain (International Journal of Advanced Engineering Research and Science, 2023)
The purpose of this paper is to explore some new fixed point results using a bilateral contraction. The first thing we need to do is recall the work on fixed-point results that have been done in different research papers. By combining the results of two papers, the first was by Rus [12], which discussed different fixed point results on a set with two metrics, and the second was by Chen [4], which used bilateral contractions to prove different fixed point results. In this paper, we present new results for single-valued mappings on a single set with two metrics. In order to accomplish all of this, a bilateral contraction of the type used by Dass Gupta has been used.